Character Education Values in Banyumulek Pottery of Lombok: From the Perspectives of the Pancasila Student Profile and Ethnopedagogy - Nurul Kemala Dewi; Eko Haryanto; Syakir Syakir; Muh. Fakhrihun Naam (LP. Ma'arif Janggan Magetan, 2025)
This study aims to analyze the character education values embedded in Banyumulek pottery of Lombok from the perspective of the Pancasila Student Profile and Ethnopedagogy. This research adopts a qualitative approach. Data collection was conducted through relevant literature reviews, observation and interviews. Data analysis employed a inductive-deductive approach. In general, an inductive approach was employed to address the research objectives by interpreting the data and explaining the findings through existing theories and literature; specifically, a deductive approach was utilized to outline the six-dimensional theory and validate its application to Banyumulek pottery. The findings reveal that six dimensions of the Pancasila Student Profile are reflected in Banyumulek pottery of Lombok, namely: 1) The Faith dimension, demonstrated through the belanger stage, obedience to Allah SWT.; 2) The Global Diversity dimension, expressed through mutual respect; 3) The Mutual Cooperation dimension, evident in the spirit of helping one anothers; 4) The Independence dimension, reflected in the self-reliance of artisans in creating pottery; 5) The Critical Reasoning dimension, indicated by the persistence in preserving pottery; and 6) The Creativity dimension, seen in the efforts to innovate by creating new pottery designs. This study offers a connection between traditional crafts and the framework of modern education.